Category of adaptation and adaptivity in the enterprises’ restructuring management theory - S.О. Shpak (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2018)
The author researches and defines more accurately the content of the concept of adaptation and adaptivity through the management issues of restructuring industrial enterprises; the article reveals the connection of these concepts with the concepts of viability, competitiveness, potential and restructuring as well as their places in the conceptual and categorical structure of enterprises’ restructuring theory. It is shown, that viability as a synthetical feature of an enterprise is determined with the ability of a lower hierarchy level, where the main ones are the ability to produce goods, to maintain production and working resources in due conditions, and the ability to be transformed; according to their content these abilities are equivalent to the corresponding potentials of economic theory of potentials. It is established that the parametric adaptivity corresponds to the management potential concept, the structural adaptivity corresponds to the development potential concept, and the process of industrial enterprise restructurization is the process of structural adaptation that provides the change of the enterprise structure as a system, any of its subsystems, and the components that is identical to the change of the system potentials in order to provide enterprise’s viability (competitiveness) as a whole, that is the ability of the enterprise to earn acceptable profit on a long basis.